Comparison of ethanolic extract of garlic with Glibenclamide on some biochemical standards in mice which diabetic mellitus - فاضل, هيام; ياسين, مفيد; شيخ يوسف, خلود (Latakia University Journal -Biological Sciences Series, 2021)
This study aimed to determine the effect of ethanolic extract of Allium sativums on the levels of glucose ,cholesterol and triglyceride in the blood serum of adult white mice with induced diabetes. This study included 40 male mice of Balb/c, which were divided into four experimental groups (10 mice per group). The results showed a significant increase (P <0.05) in the concentration of glucose, cholesterol and triglycerides in the blood serum of the group of mice injected with alloxan compared with the physiological control, and the results also showed a significant decrease (P <0.05) in the concentration of glucose, cholesterol and triglycerides in the blood serum of the group of mice. Treatment with garlic compared to control glucose. Results showed that ethanolic extract of Allium sativums has an important effect on lowering the level of biochemical to normal values equivalent to Glibenclamide.